Exercise Overrides Blunted Hypoxic Ventilatory Response in Prematurely Born Men - Debevec, Tadej; Pialoux, Vincent; Millet, Grégoire P.; Martin, Agnès; Mramor, Minca; Osredkar, Damjan (Frontiers in Physiology, 2019)
Purpose: Pre-term birth provokes life-long anatomical and functional respiratory system sequelae. Although blunted hypoxic ventilatory response (HVR) is consistently observed in pre-term infants, it remains unclear if it persists with aging and, moreover, if it influences hypoxic exercise capacity. In addition, it remains unresolved whether the previously observed prematurity-related alterations in redox balance could contribute to HVR modulation. Methods: Twenty-one prematurely born adult males (gestational age=29 ± 4) weeks), and 14 age matched controls born at full term (gestational age=39 ± 2 weeks) underwent three tests in a randomized manner: 1) hypoxia chemo-sensitivity test to determine the resting and exercise poikilocapnic HVR and a graded exercise test to volitional exhaustion in 2) normoxia (FiO2=0.21) and 3) normobaric hypoxia (FiO2=0.13) to compare the hypoxia-related effects on maximal aerobic power (MAP). Selected prooxidant and antioxidant markers were analyzed from venous samples obtained before and after the HVR tests. Results: Resting HVR was lower in the pre-term (0.21 ± 0.21 L·min-1·kg-1) compared to full-term born individuals (0.47 ± 0.23 L·min-1·kg-1; p0.05). No differences were noted in the exercise HVR or in any of the measured oxidative stress markers before or after the HVR test. Hypoxia-related reduction of MAP was comparable between the groups. Conclusions: These findings indicate that blunted resting HVR in prematurely born men persists into adulthood. Also, active adults born prematurely seem to tolerate hypoxic exercise well and should, hence, not be discouraged to engage in physical activities in hypoxic environments. Nevertheless, the blunted resting HVR and greater desaturation observed in the pre-term born individuals warrant caution especially during prolonged hypoxic exposures.